2017
DOI: 10.1017/s0952675717000069
|View full text |Cite
|
Sign up to set email alerts
|

Moro vowel harmony: implications for transparency and representations

Abstract: This paper describes and analyses the vowel-harmony system of the Kordofanian language Moro. Moro has a cross-height dominant-recessive raising harmony system in which high vowels and a central mid vowel trigger harmony, while peripheral mid vowels and a central low vowel are harmony targets. Schwas can co-occur with any of the vowels, appearing inert to harmony. Yet when schwas occur alone in a morpheme, some trigger harmony and some do not. We suggest that an original ATR-harmony system shifted to a height s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…Similarly, Benus and Gafos (2007) find small articulatory and acoustic differences in Hungarian /i/ based on backness context, arguing that these vowels are not truly transparent at the phonetic level. Unlike the small, decidedly phonetic effects reported for Finnish and Hungarian, Gick et al (2006) and Ritchart and Rose (2017) report much more salient alternations in Kinande and Moro. In Kinande, the low vowel /a/ is produced with lower F1, and with significantly advanced tongue root in [+ATR] contexts; Gick and colleagues propose that underlying /a/ phonologically alternates with surface [ə].…”
Section: Pseudo-transparencycontrasting
confidence: 69%
See 2 more Smart Citations
“…Similarly, Benus and Gafos (2007) find small articulatory and acoustic differences in Hungarian /i/ based on backness context, arguing that these vowels are not truly transparent at the phonetic level. Unlike the small, decidedly phonetic effects reported for Finnish and Hungarian, Gick et al (2006) and Ritchart and Rose (2017) report much more salient alternations in Kinande and Moro. In Kinande, the low vowel /a/ is produced with lower F1, and with significantly advanced tongue root in [+ATR] contexts; Gick and colleagues propose that underlying /a/ phonologically alternates with surface [ə].…”
Section: Pseudo-transparencycontrasting
confidence: 69%
“…First, in a number of languages with reported transparency, phonetic studies have shown that the 'transparent' vowels actually alternate for harmony (Gordon, 1999;Gick et al, 2006;Benus & Gafos, 2007;Ritchart & Rose, 2017). Gordon (1999) examines putatively transparent /e/ and /i/ in Finnish, reporting small (up to 100 Hz) differences in the second formant based on backness context.…”
Section: Pseudo-transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…The status of the preverb as a clitic can be attributed to its P specification, which forces it to attach to a word (X-[ ω ), as with Serbo-Croatian clitics (13). However, the preverb still is able to phonologically interact with its host, undergoing stem-controlled vowel-height harmony (Rose 2013;Ritchart and Rose 2017), seen in the alternation between D-a= in (20a) vs. D-3= in (20b). Such cross-phasal phonological interactions are predicted to occur in phase-based spellout as long as they are of a purely phonological nature and are not triggered by a cophonology or prosodic requirement of the lower phase, as detailed in Sect.…”
Section: Cophonologies By Phasementioning
confidence: 99%
“… 8 In prior research on Moro, this suffix was transcribed as [-ət̪]. New acoustic analysis (Ritchart & Rose 2015, 2017) shows that the vowel is more appropriately transcribed as [ɘ]. …”
mentioning
confidence: 99%